TATA CARA, TEKNIS, DAN TAHAPAN PEMBUATAN PERUNDANG-UNDANGAN - Akhmad Zaki Yamani (INTELIGENSIA MEDIA, 2024)
The legislative process is a crucial element within a country's legal system, playing a vital role in establishing fair, effective, and practical regulations for society. This article explores the fundamental concepts, stages of development, technical aspects of drafting, as well as the obstacles and challenges encountered in the legislative process. In the context of fundamental concepts, legislation is defined as a series of legal norms that govern societal life, with the primary goal of establishing order and justice. The stages of legislative development include initiation, deliberation, legislation, implementation, and evaluation, conducted while adhering to principles of good law and inclusive community participation. Additionally, technical aspects such as clear language use, organized document structures, and appropriate legislative techniques are integral parts of the drafting process. However, the legislative process often faces obstacles and challenges such as resource limitations, conflicts of interest, and legal complexities. With an awareness of these challenges, policymakers are expected to take appropriate measures to overcome them and ensure the smooth development of effective and efficient policy-making processes